Licensing digital content a practical guide for librarians - Harris, Lesley Ellen; IG Publishing (Chicago American Library Association, 2009)
Provides an overview of issues surrounding electronic media access licenses for librarians.
When to license -- Demystifying the licensing experience -- Learning the lingo -- Key digital licensing clauses -- Boilerplate clauses -- Un-intimidating negotiations -- Questions and answers on licensing -- Go license!.
Electronic reproduction.
Keywords: Copyright -- Electronic information resources -- United States; License agreements; Libraries and electronic publishing; Acquisition of electronic information resources -- United States; Electronic books